Impact behavior of composite hollow sphere structures - Vesenjak, M. (SAGE Publications, 2009)
Porous composite materials constitute an innovative group of lightweight materials which combine high specific stiffness, good damping properties, and thermal insulation with the ability to absorb large amounts of energy at a low constant stress level. In the scope of this study, adhesively bonded metallic hollow sphere structures (MHSS) fully embedded within the adhesive matrix are considered with aim to determine their macroscopic behavior under uniaxial impact loading conditions by means of parametric computational simulations. The base material properties have been determined by quasi-static and dynamic experiments. Three topologies of syntactic hollow sphere structures of various dimensions are considered, namely the cubic primitive, the body centered cubic and the face centered cubic topology. Results of computational simulations show significant influence of topology and strain rate sensitivity on the composite structure behavior, while the influence of metallic hollow sphere wall thickness is less pronounced. Computational simulations show that it is possible to combine the MHSS topology, metallic hollow sphere wall thickness and strain rate sensitivity to achieve any desired dynamic response of MHSS adapted to a given engineering problem.